A New Versatile Route to the Synthesis of a Novel Series of Highly Substituted 1,1′-Carbonylbispyrazole Derivatives - Saberi, Sattar; Eshghi, Hossein; Rahimizadeh, Mohamad; Abnous, Khalil (Synlett, 2014)
The reaction of 1H-pyrazole-1-carbohydrazide with various α,β-unsaturated nitriles under suitable conditions leads to a cyclocondensation reaction, thereby providing a novel route for the synthesis of a series of highly substituted 1,1′-carbonylbispyrazole derivatives.
Keywords: 1H-pyrazole-1-carbohydrazide; pyrazoles; α,β-unsaturated nitriles; carbonylbispyrazoles; cyclizations; heterocycles